2019
DOI: 10.1186/s12864-019-5634-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic reprogramming of barley seminal roots by combined water deficit and salt stress

Abstract: Background Water deficit and soil salinity substantially influence plant growth and productivity. When occurring individually, plants often exhibit reduced growth resulting in yield losses. The simultaneous occurrence of these stresses enhances their negative effects. Unraveling the molecular mechanisms of combined abiotic stress responses is essential to secure crop productivity under unfavorable environmental conditions. Results This study examines the effects of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 64 publications
5
43
0
Order By: Relevance
“…It can be seen that the individual stress type and duration have important impacts on the number of DEGs, which correlated well with a previous study. 51,52 In addition, more DEGs can be identied for yellow horn in response to low temperature stress than to salt treatment and ABA treatment, implying yellow horn may have strong defensive systems in response to low temperature environment. Meanwhile, DEGs regulated by different abiotic stresses at different time points exhibited a conservation of 27% to 45% to large extent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the individual stress type and duration have important impacts on the number of DEGs, which correlated well with a previous study. 51,52 In addition, more DEGs can be identied for yellow horn in response to low temperature stress than to salt treatment and ABA treatment, implying yellow horn may have strong defensive systems in response to low temperature environment. Meanwhile, DEGs regulated by different abiotic stresses at different time points exhibited a conservation of 27% to 45% to large extent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, several groups have started to overcome the technical issues that are encountered in designing the experimental set-up of combined stress factors under controlled conditions in the laboratory. Thus, in addition to two pioneering studies by Rizhsky et al (2002Rizhsky et al ( , 2004 on the effects of combined heat and drought stresses on gene expression profiles in tobacco and Arabidopsis, several recent genome-wide studies have made a shift to investigate plant responses to combined stresses (Rasmussen et al, 2013;Prasch and Sonnewald, 2013;Sewelam et al, 2014;Barah et al, 2016;Georgii et al, 2017;Shaar-Moshe et al, 2017;Osthoff et al, 2019). These studies suggested that plant molecular response to different individual stresses could not be used to predict the plant responses to combined stress treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Then they were incubated in darkness at 30 °C over night to induce germination and only germinating seeds were used for further experiments. Growth in rhizoboxes for plant phenotyping and rotation experiments were conducted as described before (46). For phytohormone treatments, plants were grown on half-strength Hoagland solution (47), pH 5.8, supplemented with 0.8% phytagel on square Petri dishes, which were placed in a 45° angle.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%